Enhancing the biochemical potential of holy basil through methyl jasmonate elicitation with insights into physiological responses in a plant factory - Panita Chutimanukul; Akira Thongtip; Atikorn Panya; Natthaporn Phonsatta; Sujichon Thangvichien; Kriengkrai Mosaleeyanon; Praderm Wanichananan; Wannida Sae-Tang; Preuk Chutimanukul (Scientific Reports)
Abstract This study investigated the effects of methyl jasmonate (MeJA) on secondary metabolite production in Ocimum tenuiflorum L. in a plant factory. MeJA concentrations ranging from 250 to 1000 ppm were administered, assessing their impact on bioactive compounds such as total phenolic content (TPC), total flavonoid content (TFC), anthocyanins, and volatile organic compounds (VOCs) including β-caryophyllene, α-humulene, and linalool over 12 days. The findings revealed that 250–500 ppm MeJA significantly boosted TPC and TFC, especially on 8 and 12 days after treatment, optimizing antioxidant levels without compromising plant health. Higher concentrations (750–1000 ppm) effectively increased anthocyanin and eugenol content shortly after treatment, with notable increases in β-caryophyllene, α-humulene, and linalool at 500 and 750 ppm, respectively, at 12 days after treatment. Physiological adjustments were also evident; while lower concentrations of MeJA modified transpiration rate and enhanced water use efficiency (WUE), they did not significantly affect photosynthetic rate or biomass. Additionally, correlation and clustering analysis demonstrated significant relationships between physiological markers, spectral indices, and metabolite accumulation, highlighting the potential to integrate elicitation techniques with environmental management to enhance bioactive chemical production. MeJA may serve as an elicitor to improve the nutritional and medicinal value of crops in controlled environments, with possible applications in sustainable agricultural practices.